Industrial training report: Information Technology Department on Universiti Teknologi MARA Campus Segamat / Nur Amira Salim - Salim, Nur Amira (Perpustakaan Tengku Anis, 2017)
The industrial training report based on the period from 2nd February 2017 until 30th June 2017 in undergoing Information Technology department at University Technology Mara Campus Segamat Department that focusing on system and record development. In this industrial training report the student will be discussing regarding the period starting with the organization introductory followed with department introduction along business tasks. In this report it was highlighted about the training activities, experiences skills and challenges that the student has been encountered. All training activities and special project are recorded in this industrial training report. The student has been involved in creating corporate branding which demanding the ability of the student to create powerful and impactful corporate branding. The special project that been given must be fulfill during the period.